Information technology entrepreneurship and innovation - Zhao, Fang, 1956- (Hershey PA : Information Science Reference, 2008)
'This book presents current studies on the nature, process and practice of entrepreneurship and innovation in the development, implementation, and application of information technology worldwide, as well as providing academics, entrepreneurs, managers, and practitioners with up-to-date, comprehensive, and rigorous research-based articles on the formation and implementation of effective strategies and business plans'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references (p. 451-494) and index.
Keywords: Information technology; Electronic commerce; Technological innovations; Entrepreneurship